JARGONITIS AS SEEN ON “AQUA” BOTTLE - Hendra Hendra (FKIP, Universitas Banten Jaya, 2018)
This research is aimed to describe the jargonitis created by PT Danone as the company producing “Aqua.” Then, the analysis was based on the cohesion and coherences provided on the label of “Aqua.” The jargonitis was created by the company to attract the market target, in this case the teenagers as the largest consumers in the world. In a business world, there are some efforts conducted by a company for the products released can be effective for some people, inthis case, to attract some people. The effective method to conduct the efforts is by marketing. One of the methods done by a mineral water company is by creating jargonitis. Therefore, some people will remember the jargon with the purpose of the company that “someone could not focus if the were dehydrated.” The study used content analysisi method. As the results of the research are the meaning of Jargontitis that it can be divided into three parts; 1) Onomatopoeic based Jargon; 2) Blend and Acronym based Jargon; and 3)Pidgin Based Jargon. Therefore, some teenagers will use the jargons in their activities and indirectly they will remember “Aqua” as the focus maker.